Two generations of digital natives - Linne, Joaquín Walter (2014)
From surveys, interviews and observations in the Autonomous City of Buenos Aires, we assert that there are two generations of digital natives (ND): young people 1.0 and 2.0. Although both share common characteristics, the 2.0 has particular characteristics: they are a post-mail generation, often growing up around digital environments and they tend to share intimacy aspects in an online mode. These personal images and texts, which they share with their peer group through social networking sites, express a new conception of privacy that we can call "multimidad". Also, we divided the ND 2.0 according to their level of digital literacy, conditioned by its technological environment, its cultural capital and their uses of ICT, with the aim of providing analytical tools to help improve public policies of digital inclusion.